1995
DOI: 10.1183/09031936.95.08081352
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic and inflammatory processes in pleural effusions

Abstract: F Fi ib br ri in no ol ly yt ti ic c a an nd d i in nf fl la am mm ma at to or ry y p pr ro oc ce es ss se es s i in n p pl le eu ur ra al l e ef ff fu us si io on ns s F. Philip-Joët*, M-C. Alessi**, C. Philip-Joët**, M. Aillaud**, J-R. Barriere*, A. Arnaud*, I. Juhan-Vague** Sixty patients with pleural effusion were studied. The underlying aetiology was empyema in 10 cases, tuberculosis in 9, cancer in 31, cardiac failure in 7, and undetermined in 3. Plasminogen, plasminogen activator inhibitor 1 (PAI-1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 14 publications
(20 reference statements)
4
37
0
Order By: Relevance
“…The fibrinolytic system, which is responsible for fibrin balance, is regulated by a precise interplay between activators and inhibitors [20,21]. The plasminogen activators (PAs), tissue-type PA (t-PA) and urokinase PA (u-PA) modulate the activation of the inactive plasminogen precursor, which results in fibrin digestion and the production of soluble degradation products (D-dimer).…”
Section: Introductionmentioning
confidence: 99%
“…The fibrinolytic system, which is responsible for fibrin balance, is regulated by a precise interplay between activators and inhibitors [20,21]. The plasminogen activators (PAs), tissue-type PA (t-PA) and urokinase PA (u-PA) modulate the activation of the inactive plasminogen precursor, which results in fibrin digestion and the production of soluble degradation products (D-dimer).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with CPE, high intrapleural levels of both t-PA, u-PA and their inhibitors (PAIs) have been found [7]. Intrapleural hypofibrinolysis, owing mainly to excessive concentration of inhibitors, has been postulated [1].…”
Section: Discussionmentioning
confidence: 98%
“…Though many reports have shown that pleural inflammatory response is mediated by the release of potent proinflammatory cytokines and fibrin deposition usually following pleural inflammation, the association between cytokines and the fibrinolytic system in pleural effusions is poorly understood [7,8,[21][22][23]. Intrapleural fibrinolytic therapy is a useful model to study the relationship of proinflammatory cytokines and fibrinolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic action of r-tPA in the CPE is probably related to the pathogenesis of fibrin deposition in exudative pleural effusions, which includes an imbalance of coagulant and fibrinolytic activity secondary to a decreased level of endogenous r-tPA in the pleural fluid, and to the inhibition of plasminogen and plasmin by plasminogen activator inhibitors 1 and 2 and by other mediators [7,8]. r-tPA acts by breaking the fibrin loculations allowing easier drainage of the pleural fluid.…”
Section: Discussionmentioning
confidence: 99%